Development of Battery Materials to Function as Corrosion Protection on Car Body Plates - Rohmannudin, Tubagus Noor; Sulistijono, Sulistijono; Adrinanda, Noval; Dharma, Faridz Wira; Areliano, Samuel (UI Scholars Hub, 2023)
Most car bodies made for mass production are made from steel or aluminum. Both are strong metals, but steel is cheaper than aluminum and is more commonly used in lower-end cars for a broader consumer range. The weakness of steel compared to aluminum is that it is susceptible to corrosion under certain conditions, and thus it may deteriorate over time without proper care. To prevent corrosion, modern cars are coated with paint to prevent direct contact with the environment. As a second line of protection, a car battery can be connected to the body to create an impressed current cathodic protection circuit. In this study, a steel sample from the car body is connected to an ICCP or impressed current cathodic protection circuit with a small 12v battery and a graphite anode. The specimen's paint layers are removed through grinding and tested in water, wet soil, and open air. The specimens in water and wet soil experienced minimum corrosion during the testing period, while the ones in open air experienced significant corrosion products on the surface. Overall, due to the small specimen size compared to battery output, all specimens experience a case of overprotection of up to -5516 mv in wet soil and -2666 mv in water. Due to limitations, we are unable to do proper measurements in the open-air environment.